Partnership Planning For M and E and Performance of Public Agricultural Projects in Galana Kilifi County, Kenya (International Journal of Scientific Research in Science and Technology, 2025)
Performance of public agricultural projects in Galana, Kilifi County is viewed in terms of food security, reduction in food prices, creation of jobs through production, agro-processing, packaging, distribution, exportation and tourism. Success of M&E System among pioneer countries of Australia, Chile, Colombia and China is attributed to Partnership planning for M&E. In as much as the Kenyan constitution recognizes the right of every person to be free from hunger and have adequate food of acceptable quality and quantity, vision 2030 aims to make Kenya a rapidly industrializing country by 2030 seems unrealistic since performance of public agricultural projects in Kenya is marred with food insecurity, rising food prices, poverty due to lack of employment in growth of agro-processing, packaging, distribution, exportation and tourism industries. The purpose of this study was to establish how Partnership Planning for M&E influence performance of public agricultural projects in Galana Kilifi County, Kenya. The objective of the study was to assess the extent to which partnership planning for M&E influence performance of public agricultural projects in Galana, Kilifi county, Kenya. The significance of the study is of the sense that the government, farmers, extension agents and the community are expected to benefit from this study since the components of Partnership planning for M&E will optimize productivity, enhance effective resource management and achieve the agenda of food security. The study adopted pragmatic paradigm with mixed methods research approach, using descriptive survey research design and correlation. A total of 226 research respondents, composed of 21 senior level managers, 82 middle level managers and 123 junior level managers, participated in the study drawn from a population of 550 respondent guided by Krejcie and Morgan theory of sample size determination. Self-administered questionnaires and an interview guide was used to collect quantitative and qualitative data. To ensure validity and reliability of the research instruments, pilot testing was conducted prior among 23 participants. Cronbach’s alpha at α =0.870 was attained as the reliability coefficient of the pre-test retest of instruments. Descriptive and inferential statistics were used to analyze data. Simple and multiple linear regression and Pearson Correlation Coefficient models were used to determine the extent to which Partnership Planning for M&E influence performance of public agricultural projects. Tests of statistical assumptions were carried out before data analysis to avoid invalidation of statistical analysis. The hypothesis was tested at α=0.05 level of significance. Results shows that: 1.HO: Partnership planning for M&E does not significantly influence performance of public agricultural projects was rejected since P-value=0.000<0.05. The study concluded that there is a significant influence of partnership planning for M&E on the performance of public agricultural projects.